The Use of Social Media as a Strategy for the Development of MSMEs in Indonesia - Asmar Asmar; Nurul Emil Safitri; Mukarramah Syukur; Adriansyah Adriansyah (Universitas Negeri Makassar, 2026)
This study aims to analyze the use of social media as a strategy for the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The study employs a descriptive qualitative approach focusing on the experiences of MSME actors in utilizing social media for promotion, communication with consumers, and market development. Data were collected through in-depth interviews, observation, and documentation involving MSME actors who actively use social media in their business activities. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that social media is used by MSMEs as an affordable and effective promotional tool, a medium for direct interaction with consumers, and an instrument for building business image. However, its utilization has not been fully optimized due to challenges such as limited digital literacy, lack of time for content management, and intense competition in digital markets. This study demonstrates that social media plays an important role in supporting MSME development, but its success is highly dependent on the ability of business actors to manage digital communication strategies consistently and adaptively.